Optimal intervention strategies for an epidemic: A household view. (December 2013) - Yarmand, Hamed; Ivy, Julie S
In this research, we identify optimal intervention strategies at the household level in case of an epidemic. We consider an affected household (a household with one initial infective member) and model the effect of different intervention policies, which involve vaccination, antiviral prophylaxis, isolation, and treatment, on disease spread using a variation of Kermack–McKendrick (KM) models. Both full and partial adherence to interventions are considered. An implementation cost is assumed for each intervention policy. We refer to a collection of intervention policies as an intervention strategy. A reward is associated with susceptible members who remain uninfected. We define the effect of the implemented intervention strategy as the total reward earned by all members over the time horizon. We then identify the most cost-effective intervention strategies. In addition, we incorporate a budgetary constraint for the household and find the efficient frontier for the total reward over different upper bounds on the household budget.